Long‐term safety and efficacy of imeglimin as monotherapy or in combination with existing antidiabetic agents in Japanese patients with type 2 diabetes (TIMES 2): A 52‐week, open‐label, multicentre phase 3 trial. Issue 4 (27th December 2021) - Dubourg, Julie; Fouqueray, Pascale; Quinslot, Damien; Grouin, Jean‐Marie; Kaku, Kohei
Abstract: Aim: To evaluate the safety and efficacy of imeglimin for 52 weeks as monotherapy or combination therapy with existing antidiabetic agents in Japanese patients with type 2 diabetes. Materials and Methods: TIMES 2 was a phase 3, pivotal, open‐label trial including patients with type 2 diabetes inadequately controlled despite diet/exercise or despite treatment with a single agent from one of several available classes of antidiabetic drugs along with diet/exercise. All patients received imeglimin 1000 mg twice‐daily orally for 52 weeks as monotherapy or combination therapy. The primary endpoint was safety (adverse events, laboratory results, ECG). The secondary endpoints were changes from baseline in HbA1c and fasting plasma glucose at week 52. Results: A total of 714 patients received the following treatments: imeglimin monotherapy (n = 134), combination with an α‐glucosidase inhibitor (n = 64), biguanide (n = 64), dipeptidyl peptidase‐4 inhibitor (DPP4‐I; n = 63), glinide (n = 64), glucagon‐like peptide‐1 receptor agonist (GLP1‐RA; n = 70), sodium‐glucose co‐transporter‐2 inhibitor (n = 63), sulphonylurea (n = 127), or thiazolidinedione (n = 65). The percentage of patients experiencing at least one treatment emergent adverse event (TEAE) was 75.5%. Most of these events were mild or moderate in intensity. Serious TEAEs, none of them related to the study drug, occurred in 5.6% of all patients. No clinically significant changes in ECG, vital signs, physical examination, or laboratory tests were noted in any groups. At week 52, HbA1c decreased by 0.46% with imeglimin monotherapy, by 0.56%‐0.92% with imeglimin as oral combination therapy, and by 0.12% with injectable GLP1‐RA combination therapy. The greatest net HbA1c reduction (0.92%) occurred in patients receiving a DPP4‐I in combination with imeglimin. Conclusions: Imeglimin provides well‐tolerated, long‐term safety and efficacy in both monotherapy and oral combination therapy in Japanese patients with type 2 diabetes.